In Memoriam – Professor Ignacy GLOZA - Eugeniusz KOZACZKA; Grażyna GRELOWSKA (Archives of Acoustics, 2016)
On 4th November 2016 Professor Ignacy Gloza passed away. He was a wonderful person, still full of creative powers, committed to researchwork in hydroacoustics carried out in cooperation with Polish and foreign research institutes.